The NHS Health Check programme: a survey of programme delivery in England before and after the Covid-19 pandemic response - Gadsby, EW; Krska, J; Duddy, C; Hibberd, V; Wong, G (F1000Research, 2023)
Background: This study investigated NHS Health Check programme delivery before and after the Covid-19 pandemic response, with a focus on support services and referral methods available to Health Check attendees. The NHS Health Check is an important part of England’s Cardiovascular Disease (CVD) prevention programme.